Weighted Composition Operators from Hardy to Zygmund Type Spaces - Shanli Ye; Zhengyuan Zhuo (Abstract and Applied Analysis)
This paper aims at studying the boundedness and compactness of weighted composition operator between spaces of analytic functions. We characterize boundedness and compactness of the weighted composition operator from the Hardy spaces to the Zygmund type spaces and the little Zygmund type spaces in terms of function theoretic properties of the symbols and .